Serum apolipoproteins in relation to intakes of fish in population of Arkhangelsk County - Petrenya, Natalia Nikolaevna; Brustad, Magritt; Cooper, Marie; Dobrodeeva, Lilya; Bichkaeva, Fatima; Lutfalieva, Gulnara; Odland, Jon Øyvind (Nutrition & Metabolism, 2012)
Diets rich in omega-3 fatty acids and low in saturated fat were found beneficially associated with blood lipids and cardio-vascular health. Lean reindeer meet and local cold water white-fish species high in omega-3 are among the main sources of nutrients in the rural area of the Nenets Autonomous Okrug (NAO) in Russia and are not normally consumed by the urban population from the same region. The aims of the study were firstly, to compare serum lipid profiles of residents of urban (Arkhangelsk city) and rural (NAO) regions of Arkhangelsk County, and secondly, to investigate the effects of fish consumption on the predictor of cardiovascular events apolipoprotein (Apo) B/ApoA-I ratio in these populations. A cross-sectional study conducted in Arkhangelsk County, Russia. Sample size of 249 adults: 132 subjects from Arkhangelsk city, aged 21–70 and 117 subject (87% Ethnic Nenets) from NAO, aged 18–69. We observed more favorable lipid levels in NAO compared to Arkhangelsk participants. Age-adjusted geometric means of ApoB/ApoA-I ratio were 1.02 and 0.98 in men and women from Arkhangelsk; 0.84 and 0.91 in men and women from NAO respectively. Age and consumption of animal fat were positively associated with ApoB/ApoA-I ratio in women (pooled samples from Arkhangelsk and NAO). Body mass index and low levels of physical activity were positively associated with ApoB/ApoA-I ratio in men (pooled samples from Arkhangelsk and NAO). Reported oily fish consumption was not significantly correlated with ApoB/ApoA-I ratio. The population sample from rural NAO, consisting largely of the indigenous Arctic population Nenets with healthier dietary sources, had a relatively less atherogenic lipid profile compared to the urban Arkhangelsk group. Fish consumption had no effect on apolipoproteins profile.